The influence of Hydrogen on Nickel Alloy 625 Manufactured using Direct Energy Deposition - Kovacs, Alex; Salasi, Mobin; Quadir, Zakaria; Hutchinson, C.; Sapanathan, Thaneshan (2024)
Nickel Alloy 625 (UNS N06625) is an austenitic material which is primarily strengthened by solid solution. It is commonly used for high temperature applications and in corrosive environments and is often used as a corrosion resistant alloy (CRA) in the Oil and Gas industry. In subsea Oil and Gas applications, Nickel alloys such as UNS N06625 can be connected to less noble materials which are protected by cathodic protection (CP), because of this hydrogen will evolve from the surface of these materials and can adsorb and diffuse into the Nickel alloys which can lead to hydrogen embrittlement and ultimately a failure of the material. This study develops insight into hydrogen behaviour of UNS N06625 which is manufactured using Direct Energy Deposition (DED) and is compared with the conventionally manufacturing method. The hydrogen embrittlement susceptibility is assessed using step loading tensile tests (SLTT) based on ASTM F1624-12 standard. The tensile samples were pre-charged with hydrogen in a 0.6M NaCI environment at 50mA galvanostatic current, equivalent to -1.4V Ag/AgCI and were continually charged in-situ during loading until failure. The results indicate that DED produces an increased hydrogen embrittlement resistance compared to conventionally manufactured UNS N06625 with fractography analysis indicating hydrogen behaviour differences between the two manufacturing methods. Keywords: Hydrogen Embrittlement, Inconel 625, Direct Energy Deposition, Additive Manufacturing, Cathodic Protection